Lipids, Apolipoproteins, Lipid‐Lowering Drugs, and the Risk of Cerebral Small Vessel Disease: A Mendelian Randomization Study - Yi Xie; Shuai Liu; Xinyue Wang; Hao Huang; Minghuan Wang; Wensheng Qu; Zhiyuan Yu; Wei Wang; Xiang Luo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Serum lipids are causally involved in the occurrence of atherosclerosis, but their roles in cerebral small vessel disease remain unclear. This study aimed to investigate the causal roles of lipid or apolipoprotein traits in cerebral small vessel disease and to determine the effects of lipid‐lowering interventions on this disease. Methods and Results Data on genetic instruments of lipids/apolipoproteins, as well as characteristic cerebral small vessel disease manifestations, including small vessel stroke (SVS) and white matter hyperintensity (WMH), were obtained from publicly genome‐wide association studies. Through 2‐sample Mendelian randomization analyses, it was found that decreased levels of high‐density lipoprotein cholesterol (odds ratio [OR], 0.85, P=0.007) and apolipoprotein A‐I (OR, 0.83, P=0.005), as well as increased level of triglycerides (OR, 1.16, P=0.025) were associated with a higher risk of SVS. A low level of high‐density lipoprotein cholesterol (OR, 0.93, P=0.032) was associated with larger WMH volume. Specifically, the genetically determined expressions of lipid fractions in various size‐defined lipoprotein particles were more closely related to the risk of SVS than WMH. Moreover, it was found that the hypertension trait ranked at the top in mediating the causal effect of hyperlipidemia on SVS and WMH by using Mendelian randomization‐based mediation analysis. For drug‐target Mendelian randomization, the low‐density lipoprotein cholesterol‐reducing genetic variation alleles at HMGCR and NL1CL1 genes and the high‐density lipoprotein cholesterol‐raising genetic variation alleles at the CETP gene were predicted to decrease the risk of SVS. Conclusions The present Mendelian randomization study indicates that genetically determined hyperlipidemia is closely associated with a higher risk of cerebral small vessel disease, especially SVS. Lipid‐lowering drugs could be potentially considered for the therapies and preventions of SVS rather than WMH.